2019
DOI: 10.1002/micr.30472
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical reconstruction of the isolated columellar defect with a prelaminated radial forearm free flap. A case report and a review of the literature

Abstract: The columella is one of the smallest subunits of the nose, but the loss of this structure has important aesthetic and structural implications. Few papers in literature present microsurgical techniques for the reconstruction of an isolated columellar defect. This report describes the use of a prelaminated radial forearm free flap (RFFF) for the reconstruction of an isolated columellar defect and reviews the current literature. A 45‐year‐old woman presented to our Unit with a history of palate squamous cell carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
(36 reference statements)
0
11
0
Order By: Relevance
“…A total of 19 studies was included in this systematic review, as showed by the PRISMA flow diagram (Figure 1 ) (Alves et al, 2020 ; Chiarini et al, 2002 ; Collar & Byrne, 2013 ; Colletti et al, 2012 ; Jehn et al, 2019 ; Kilinc & Aytekin, 2014 ; Kim et al, 2013 ; Lauer et al, 2001 ; Maruccia et al, 2020 ; Nehrer‐Tairych et al, 2002 ; Poeschl et al, 2003 ; Rath et al, 1999 ; Sadigh & Jeng, 2015 ; Schlenz et al, 2001 ; Teng et al, 2005 ; Upton et al, 1994 ; Wolff et al, 1996 ; Ziegler & Oyer, 2021 ). Seven out of the selected 19 articles were case reports (Alves et al, 2020 ; Collar & Byrne, 2013 ; De Santis et al, 2020 ; Maruccia et al, 2020 ; Sadigh & Jeng, 2015 ; Teng et al, 2005 ; Ziegler & Oyer, 2021 ), while the remaining 12 articles were case series (with five out of them including less than five cases) (Chiarini et al, 2002 ; Colletti et al, 2012 ; Jehn et al, 2019 ; Kilinc & Aytekin, 2014 ; Kim et al, 2013 ; Lauer et al, 2001 ; Nehrer‐Tairych et al, 2002 ; Poeschl et al, 2003 ; Rath et al, 1999 ; Schlenz et al, 2001 ; Upton et al, 1994 ; Wolff et al, 1996 ). The whole study population was represented by 102 patients (63 males, 30 females, 9 not specified) undergoing reconstruction of an anatomical defect secondary to oncological ablative surgery with a prelaminated flap, over the last 27 years (1994–2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 19 studies was included in this systematic review, as showed by the PRISMA flow diagram (Figure 1 ) (Alves et al, 2020 ; Chiarini et al, 2002 ; Collar & Byrne, 2013 ; Colletti et al, 2012 ; Jehn et al, 2019 ; Kilinc & Aytekin, 2014 ; Kim et al, 2013 ; Lauer et al, 2001 ; Maruccia et al, 2020 ; Nehrer‐Tairych et al, 2002 ; Poeschl et al, 2003 ; Rath et al, 1999 ; Sadigh & Jeng, 2015 ; Schlenz et al, 2001 ; Teng et al, 2005 ; Upton et al, 1994 ; Wolff et al, 1996 ; Ziegler & Oyer, 2021 ). Seven out of the selected 19 articles were case reports (Alves et al, 2020 ; Collar & Byrne, 2013 ; De Santis et al, 2020 ; Maruccia et al, 2020 ; Sadigh & Jeng, 2015 ; Teng et al, 2005 ; Ziegler & Oyer, 2021 ), while the remaining 12 articles were case series (with five out of them including less than five cases) (Chiarini et al, 2002 ; Colletti et al, 2012 ; Jehn et al, 2019 ; Kilinc & Aytekin, 2014 ; Kim et al, 2013 ; Lauer et al, 2001 ; Nehrer‐Tairych et al, 2002 ; Poeschl et al, 2003 ; Rath et al, 1999 ; Schlenz et al, 2001 ; Upton et al, 1994 ; Wolff et al, 1996 ). The whole study population was represented by 102 patients (63 males, 30 females, 9 not specified) undergoing reconstruction of an anatomical defect secondary to oncological ablative surgery with a prelaminated flap, over the last 27 years (1994–2021).…”
Section: Resultsmentioning
confidence: 99%
“…Besides the oral cavity, significant conclusions about the advantages and limitations of the reconstruction of other anatomical sites (e.g., tracheal, nasal and auricular defect) by prelaminated flaps cannot be drawn. Overall, the short‐term results of prelaminated flaps in these areas have been reported as positive (Alves et al, 2020 ; Maruccia et al, 2020 ; Teng et al, 2005 ; Upton et al, 1994 ; Ziegler & Oyer, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, a vascularized bone graft could prelaminate the RFF; however, the bulk would compromise cosmesis 41 . Nasal breathing, tip projection, and reconstruction of full-thickness defects can be achieved with a prelaminated RFF with a cartilage graft from the fifth rib 42 …”
Section: Discussionmentioning
confidence: 99%
“…41 Nasal breathing, tip projection, and reconstruction of full-thickness defects can be achieved with a prelaminated RFF with a cartilage graft from the fifth rib. 42 Free UFF Hsiao et al 11 investigated the role of the UFF in nasal reconstruction. A customized foil template resembling the nasal defect is used to mark the flap on the volar aspect of the forearm.…”
Section: Rff Prelaminationmentioning
confidence: 99%
“…On other hand, Kitamura et al illustrated that the combined use of labia minora peripheral skin graft and an innervated free radial forearm flap could be an option for the reconstruction of extensive defects in the upper lip [18]. Moreover, Maruccia et al suggested that a prelaminated radial forearm free flap could be a great reconstructive choice in large defects of the columella [19]. Lin et al study also showed that a barrel-shaped design free forearm flap exhibited better results than a rectangular design for lower lip reconstruction based on social contact and function [10].…”
Section: Surgical Approachmentioning
confidence: 99%